INVENTARISASI PARASITOID TELUR WERENG BATANG COKELAT DI BEBERAPA PERTANAMAN PADI - Araz Meilin (Universitas Batanghari Jambi, 2012)
This research was conducted to determine the species of the egg parasitoids in rice fields in Klaten, Jawa Tengah and Bantul, Yogyakarta. The egg parasitoids were observed by trapping them with rice plant (Cisadane) containing eggs of N. lugens. The plants containing eggs of N. lugens were exposed in each field for two days. Ten plants of trap were placed along 300 m by transects at each location. Three species of egg parasitoids found in all rice fields were similar: Anagrus nilaparvatae, A. optabilis (Hymenoptera: Mymaridae) and Oligosita (Hymenoptera: Trichogrammatidae).Key words: egg parasitoids, rice cultivation, Nilaparvata lugens